Analisa Perpanjangan Restrukturisasi Kredit Terhadap Likuiditas Perbankan Sebelum dan Sesudah Pandemi Covid 19 - Sarikuswati, Silvia (Nusa Putra University, 2020)
Banking is a financial intermediary institution that collects funds from the public in the form of deposits and distributes them to the public in the form of credit or other forms. The very rapid spread of the Covid 19 outbreak resulted in disruptions to banking performance and financial system stability. Responding to this, the government made a credit relaxation policy through credit restructuring for debtors affected by Covid 19. This study aims to determine how the impact or effect of credit restructuring on banking liquidity before and after the Covid 19 pandemic. This study uses a comparative descriptive method with an assessment. quantitative, by collecting data to calculate liquidity ratios taken from financial reports that have been listed on the Indonesia Stock Exchange (IDX). Financial reports taken are the 3rd Quarter of 2019 before the pandemic appears and the 3rd Quarter of 2020 when the pandemic occurs. The results of this study indicate that from 10 samples of data obtained from financial reports by calculating the liquidity ratio, it shows that the average banking company still has the ability to fulfill its obligations during this pandemic, even though the credit restructuring is extended.